Design of a Mobile-Based Waste Management Application with a Waste Identification Feature as a Public Education Medium - Dandy Cahyo Purnomo; Ahmad Hasib Satiri; Eka Aprilia Saputri; Luluk Khatimah; Hartono (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2026)
The waste problem in Indonesia requires technological solutions to raise public awareness. This study aims to design a mobile-based waste management application as a medium for public hygiene education. Using engineering methods, it has four main features: waste type identification through camera scans, waste disposal management, digital waste management literacy, and a recycled product marketplace. The design stages include system specification analysis, interface design, and functionality testing. System testing results using the System Usability Scale (SUS) method involving 10 respondents showed an average score of 76.7. Based on SUS assessment standards, this score falls into the